MMS observations and hybrid simulations of surface ripples at a marginally quasi-parallel shock - Gingell,IL; Schwartz,SJ; Burgess,D; Johlander,A; Russell,CT; Burch,JL; Ergun,RE; Fuselier,S; Gershman,DJ; Giles,BL; Goodrich,KA; Khotyaintsev,YV; et al. (Journal of Geophysical Research: Space Physics, 2017)
Simulations and observations of collisionless shocks have shown that deviations of the nominal local shock normal orientation, i.e. surface waves or ripples, are expected to propagate in the ramp and overshoot of quasi-perpendicular shocks. Here, we identify signatures of a surface ripple propagating during a crossing of Earth's marginally quasi-parallel (θBn∼45) or quasi-parallel bow shock shock on 2015-11-27 06:01:44 UTC by the Magnetospheric Multiscale (MMS) mission, and determine the ripple's properties using multi-spacecraft methods. Using two-dimensional hybrid simulations, we confirm that surface ripples are a feature of marginally quasi-parallel and quasi-parallel shocks under the observed solar wind conditions. In addition, since these marginally quasi-parallel and quasi-parallel shocks are expected to undergo a cyclic reformation of the shock front, we discuss the impact of multiple sources of non-stationarity on shock structure. Importantly, ripples are shown to be transient phenomena, developing faster than an ion gyroperiod and only during the period of the reformation cycle when a newly developed shock ramp is unaffected by turbulence in the foot. We conclude that the change in properties of the ripple observed by MMS is consistent with the reformation of the shock front over a timescale of an ion gyro-period.